2021
DOI: 10.1159/000518754
|View full text |Cite
|
Sign up to set email alerts
|

Triamcinolone Acetonide in the Treatment of Perennial Allergic Rhinitis: A post hoc Efficacy Analysis of a Phase III Study Performed in Russia

Abstract: <b><i>Introduction:</i></b> Allergic rhinitis (AR) is a disease which affects &#x3e;24% of the population in Russia. Triamcinolone acetonide (TAA) is a corticosteroid used for treating AR. This post hoc analysis assesses the efficacy of intranasal TAA in improving perennial AR (PAR) symptom scores over 4 weeks. <b><i>Methods:</i></b> NASANIF (NCT03317015) was a double-blind, parallel-group, multicenter, prospective, non-inferiority, phase III clinical trial i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
2
0
2
Order By: Relevance
“…Previous trials have shown that TAA is effective in reducing these symptoms in patients with AR [9,17], and the results of our post hoc analysis are consistent with these findings. Furthermore, we have shown that TAA provides effective and prolonged improvement of PAR symptoms in another post hoc analysis of the same trial (Karaulov et al [18], submitted).…”
Section: Discussionmentioning
confidence: 69%
“…Previous trials have shown that TAA is effective in reducing these symptoms in patients with AR [9,17], and the results of our post hoc analysis are consistent with these findings. Furthermore, we have shown that TAA provides effective and prolonged improvement of PAR symptoms in another post hoc analysis of the same trial (Karaulov et al [18], submitted).…”
Section: Discussionmentioning
confidence: 69%
“…Acupoint injection is a modified TCM treatment that combines acupuncture stimulation with the properties of Western drugs and their penetrating effects on acupoints, exerting a comprehensive therapeutic effect[ 27 ]. Triamcinolone acetonide is a long-acting glucocorticoid with potent and lasting anti-inflammatory and anti-allergic effects[ 28 ]. Local injection can inhibit the transformation of B cells into plasma cells and interfere with humoral immunity[ 29 ] Furthermore, it stabilizes the lysosomal membrane, inhibits leukocytes and macrophages from migrating outside the blood vessels, and reduces inflammation[ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Было показано, что оба варианта лечения эффективно снижали балльную оценку rTNSS [2]. В двух недавних публикациях были представлены результаты ретроспективного анализа эффективности [3] и качества жизни (КЖ) [4] в течение 28-дневного курса обоих вариантов лечения.…”
Section: интраназальный триамцинолона ацетонид эффективно облегчает н...unclassified
“…В посвященной вопросам эффективности ретроспективной публикации еженедельно оценивались изменения в значениях rTNSS для суммарной балльной оценки (диапазон: 0-16) и для каждого из ее четырех компонентов, а также процентная доля пациентов, сообщавших об уменьшении симптомов не менее чем на 50% или 75% [3]. Как суммарная балльная оценка (Рис.…”
Section: интраназальный триамцинолона ацетонид эффективно облегчает н...unclassified